The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Proceedings of the 12th International Conference on Extending Database Technology: Advances in Database Technology 2009
DOI: 10.1145/1516360.1516398
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the power of relational databases for efficient stream processing

Abstract: Stream applications gained significant popularity over the last years that lead to the development of specialized stream engines. These systems are designed from scratch with a different philosophy than nowadays database engines in order to cope with the stream applications requirements. However, this means that they lack the power and sophisticated techniques of a full fledged database system that exploits techniques and algorithms accumulated over many years of database research.In this paper, we take the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…The potential of database systems in efficient processing of continuous queries over streaming data has been explored in [19,23,10]. Authors in [19] showed that, the performance of stream processing in a standard relational database can be improved significantly by appropriate tunning and use of existing features like indices and temporary tables.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of database systems in efficient processing of continuous queries over streaming data has been explored in [19,23,10]. Authors in [19] showed that, the performance of stream processing in a standard relational database can be improved significantly by appropriate tunning and use of existing features like indices and temporary tables.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in [19] showed that, the performance of stream processing in a standard relational database can be improved significantly by appropriate tunning and use of existing features like indices and temporary tables. The work of [23,10] presented how to extend the MonetDB and PostgreSQL database systems to support stream processing, respectively. The major motivation of these works is that, by building SPEs separately from database systems, the opportunity of leveraging the existing sophisticated algorithms and techniques of databases is lost.…”
Section: Related Workmentioning
confidence: 99%
“…In the DataCell project [14] we take a different route by designing a stream engine on top of an existing relational database kernel [15]. This includes reuse of both its storage/execution engine and its optimizer infrastructure.…”
Section: Streamingmentioning
confidence: 99%
“…Following this policy, Gigascope regularly generates punctuations (''heartbeats'') in order to unblock operators like aggregation in query plans. Recently, a stream engine built on top of a column-oriented DBMS was presented in [20], proposing transitory storage of incoming tuples in suitable system tables called baskets. Items are then propagated to operators after filtering by means of predicate windows, which apply simple selection conditions on the basket data, even irrespective of their timestamp order.…”
Section: Related Workmentioning
confidence: 99%